2021
DOI: 10.1016/j.jaac.2020.07.888
|View full text |Cite
|
Sign up to set email alerts
|

Bumetanide for Core Symptoms of Autism Spectrum Disorder (BAMBI): A Single Center, Double-Blinded, Participant-Randomized, Placebo-Controlled, Phase-2 Superiority Trial

Abstract: Objective: Recent trials have indicated positive effects of bumetanide in autism spectrum disorder (ASD). We tested efficacy of bumetanide on core symptom domains using a single center, parallel-group, participant-randomized, double-blind, placebo-controlled phase-2 superiority trial in a tertiary hospital in the Netherlands. Method: Unmedicated children aged 7 to 15 years with ASD and IQ !55 were block-randomized 1:1 to oral-solution bumetanide versus placebo, titrated to a maximum of 1.0 mg twice daily for 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 38 publications
1
78
0
Order By: Relevance
“…Increased diuresis associated with bumetanide treatment could potentially jeopardize the blinding in the Phase III studies reported here. However, this effect was found to be limited in both the BAMBI study and the Phase II trial, as the psychiatrist who assessed outcome measures was blinded to the treatment (Lemonnier et al 2017 ; Sprengers et al 2020 ). Similarly, the primary endpoint in the Phase III studies is being assessed by an independent rater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased diuresis associated with bumetanide treatment could potentially jeopardize the blinding in the Phase III studies reported here. However, this effect was found to be limited in both the BAMBI study and the Phase II trial, as the psychiatrist who assessed outcome measures was blinded to the treatment (Lemonnier et al 2017 ; Sprengers et al 2020 ). Similarly, the primary endpoint in the Phase III studies is being assessed by an independent rater.…”
Section: Discussionmentioning
confidence: 99%
“…As a secondary endpoint, cognitive and neurophysiological assessments (behavioral questionnaire, neurocognitive test battery, event-related potential paradigms, and resting state paradigms) were used to identify prognostic biomarkers of bumetanide oral liquid formulation treatment, with a view to enabling a more personalized treatment approach in the future. The BAMBI study did not find that bumetanide was superior to placebo based on the primary outcome (SRS-2 total score), although a superior effect was reported based on a secondary endpoint (Repetitive Behavior Scale-Revised; Sprenger et al 2020 ). Another recent study of bumetanide in children (n = 83) with ASD aged 3 to 6 years demonstrated significant benefits compared with control, using the CARS as the primary outcome measure (Zhang et al 2020 ).…”
mentioning
confidence: 97%
“…Bruining and colleagues conclude that Bumetanide does not attenuate ASD despite a nominally significant treatment effect in repetitive behaviors (RBS) which is a core-symptom of ASD but was defined as a secondary measure in this trial 1 . Four earlier studies performed by three independent institutes, including two that are not referred to by Bruining and colleagues 2,3 , tested a total of 169 children -vs 122 placebo-have shown a significant amelioration of ASD symptomatology.…”
mentioning
confidence: 85%
“…Further, a recent large-scale clinical trial found no improvements in social or sensory symptoms after longitudinal bumetanide treatment in children with autism, as measured using the Social Responsiveness Scale-2 (SRS-2) and Sensory Profile (SP-NL) respectively, and only minor reductions in repetitive behaviors, measured by the Repetitive Behavior Scale Revised (RBS-R) [24]. Taken together, these mixed findings highlight the need to better understand bumetanide's ability to ameliorate the multiplexed symptoms of autism, and underscore the importance of objective measures of drug efficacy.…”
Section: Recent Pharmacological Studies Confirm That Acute Modulationmentioning
confidence: 99%
“…Bumetanide is thought to increase the hyperpolarizing potential of GABA by blocking NKCC1 receptors, which are responsible for Cl-entrance into the cell [20]. Further, some studies of bumetanide in humans, specifically children with autism, have shown evidence for attenuation of social symptom severity and improvement of emotion recognition [21][22][23], although, notably, these benefits are not universally observed [24]. Importantly, to date, direct evidence that bumetanide increases inhibition in the human brain is lacking, which complicates linking the reported symptomatic benefits to the drug's predicted physiological effects.…”
Section: Introductionmentioning
confidence: 99%